Immobilization of membrane proteins on solid supports using functionalized β-sheet peptides and click chemistry. Issue 15 (2nd February 2018) - Hoi, Hiofan; Jiménez Castellanos, Antonio; Aminpour, Maral; He, Yuan; Zhou, Hang; Abraham, Sinoj; Montemagno, Carlo D.
Abstract : Functionalized beta-sheet peptide for stabilization and immobilizaton of membrane proteins. Abstract : We have developed two functionalized β-sheet peptides (FBPs) and demonstrated that they can stabilize a variety of integral membrane proteins (IMPs), and most importantly allow covalent crosslinking of the IMPs onto solid supports via the highly selective click chemistry. The FBPs are promising tools for the preparation of IMP-based biomaterials or biosensors.